Bullying Perpetration and Victimization: A Test of Traditional and Cyber-Behaviors as Latent Constructs - Brosowski, Tim (Journal of interpersonal violence, 2021)
The current investigation hypothesized and tested latent bully/victim traits for physical, verbal, or relational bullying/victimization, both cyber and traditional behaviors. Data were collected from 1,356 German students who attended Grades 5 to 10: 48.4% males, 49.3% females from eight different schools in Northern Germany. Based on two samples for cross-validation (Ntraining set = 525, Nvalidation set = 525), study findings provided strong evidence of adequate model fit, both for traditional and cyber behaviors. Consistent with the current state of knowledge, bullying and victimization latent traits highly associated, more so for cyber behaviors than traditional ones. Thus, both the theoretical plausibility as well as statistical evidence support the application of latent modeling to these behaviors. Further research is needed to replicate the applied measurement models proposed in this work and to reveal moderators or measurement invariance across diverse populations. Nevertheless, the current evidence substantiates the importance of the application of a latent modeling approach to overcome known psychometric challenges of reliability and validity in bullying research.